2017
DOI: 10.1002/hon.2453
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in hematologic malignancy settings other than the allogeneic transplant

Abstract: Cytomegalovirus (CMV) infection in clinical settings other than the allogeneic transplant represents a poorly explored issue. Thus, we performed a comprehensive review of the medical literature about CMV infection in patients undergoing autologous hematopoietic stem cell transplant and in other nontransplant-related hematologic patients. In autologous hematopoietic stem cell transplant, a CMV reactivation is reported to occur in up to 41% of CMV seropositive patients, when a prospective monitoring of antigenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 100 publications
2
57
0
3
Order By: Relevance
“…2 In patients with hematologic disorders, the risk of CMV infection is markedly increased following allogeneic stem cell transplantation or autologous stem cell transplantation (ASCT) with CD34 þ -selected cells, as well as following treatment with high-dose corticosteroids, alemtuzumab, cladribine, or fludarabine, as a result of lower levels and dysfunction of natural killer (NK) cells, CD8 þ T-cells, and CD4 þ T-cells. [2][3][4] Patients with MM have increased susceptibility to infections as a result of myeloma-induced immune dysfunction, including impaired T-and NK-cell activity, and decreased polyclonal immunoglobulin production, as well as cumulative immunosuppression of anti-MM treatment regimens. 5 The incidence of CMV DNAemia, defined as presence of CMV-DNA without CMVrelated symptoms, 1 and CMV disease in patients with MM are best studied following ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In patients with hematologic disorders, the risk of CMV infection is markedly increased following allogeneic stem cell transplantation or autologous stem cell transplantation (ASCT) with CD34 þ -selected cells, as well as following treatment with high-dose corticosteroids, alemtuzumab, cladribine, or fludarabine, as a result of lower levels and dysfunction of natural killer (NK) cells, CD8 þ T-cells, and CD4 þ T-cells. [2][3][4] Patients with MM have increased susceptibility to infections as a result of myeloma-induced immune dysfunction, including impaired T-and NK-cell activity, and decreased polyclonal immunoglobulin production, as well as cumulative immunosuppression of anti-MM treatment regimens. 5 The incidence of CMV DNAemia, defined as presence of CMV-DNA without CMVrelated symptoms, 1 and CMV disease in patients with MM are best studied following ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low rate of patients with CMV-DNAemia that develop a symptomatic CMV infection, prospective monitoring of CMV titers in these patients is not recommended. 3 When CMV-DNA quantification was performed on clinical indication, the rate of symptomatic CMV infection post-ASCT ranges from 0.7% to 30.7%. 3 Bortezomib-containing induction regimens are associated with a higher incidence of CMV reactivation post-ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study performed by Marchesi et al (2013) of 80 patients with multiple myeloma treated with ASCT also reported a significantly higher rate of CMV reactivation in patients who received bortezomib and immunomodulatory therapy when compared to standard anthracycline‐based treatment (9.4% vs 1.1% P = .019), but not in patients treated with immunomodulatory therapy alone. The study concluded that patients treated with bortezomib‐based regimens were at higher risk of developing symptomatic CMV reactivation after ASCT . A more recent retrospective study performed by Hasegawa et.al (2016) of 120 patients with multiple myeloma reported a CMV infection rate of 20% and three cases of CMV disease.…”
Section: Discussionmentioning
confidence: 95%
“…A comprehensive literature review performed by Marchesi et al (2017) of non‐transplant haematology patients revealed highly variable CMV reactivation rates ranging between 2% and 39%, but this included a wide range of agents including bortezomib, bendamustine and rituximab. The CMV reactivation rate of 39% of seropositive patients in this current study is similar to the 48.5% reported by Kim et.al; although these studies are not directly comparable due to different patient populations.…”
Section: Discussionmentioning
confidence: 99%